Principals' perspectives on faculty diversity in Qatar's government schools. (September 2019) - Romanowski, Michael H.; Abu-Shawish, Reem K.; Merouani, Nora
Globalization requires the Gulf Cooperation Countries (GCC) to experience numerous economic, social, and educational changes. In particular, Qatar's unprecedented economic growth has created a flow of high- and low-skilled expatriate workers resulting in a significant imbalance between nationals and expatriates. The implications are evident in Qatar's government schools where approximately 72% of teachers are expatriates and 99% of the principals are Qatari nationals. Although diversity can enrich schools, it could create conflicts that might hamper the school's success. Despite the large body of research on school leadership and student diversity, little is written about principals and faculty diversity especially within the GCC. Semi-structured interviews were used to explore 20 Qatari principals' perspectives regarding their understandings of diversity and experiences with faculty diversity. Findings demonstrate that principals perceive diversity in terms of nationality. They experienced positive and negative influences of diversity and are confronted with challenges that often center on ethnical and cultural issues. Principals addressed how they manage the issues of nationality, culture, and equality. The study suggests that school leadership in a multicultural society such as Qatar demands more competencies to manage faculty diversity. Several recommendations are offered for principals for working with a diverse faculty.